Shortened telomere length is associated with paroxysmal atrial fibrillation among cardiovascular patients enrolled in the Intermountain Heart Collaborative Study - Carlquist, John F.; Knight, Stacey; Cawthon, Richard M.; Le, Viet T.; Jared Bunch, T.; Horne, Benjamin D.; Rollo, Jeffrey S.; Huntinghouse, John A.; Brent Muhlestein, J.; Anderson, Jeffrey L. (Heart rhythm, 2016)
Atrial fibrillation (AF) diminishes quality of life and accounts for approximately one-third of all strokes. Studies have associated mitochondrial dysfunction with both AF and telomere length (TL). The purpose of this study was to test the hypothesis of a relationship between AF and TL. Blood was collected from consenting participants in the Intermountain Heart Collaborative Study (n = 3576) and DNA extracted. TL was determined by multiplex quantitative polymerase chain reaction, normalized to a single copy gene, and reported as telomere/single gene ratio (t/s). Patient information was extracted from Intermountain Healthcare’s electronic records database. Prevalent AF was determined by discharge ICD-9 code. AF subtype (paroxysmal [Px], persistent [Ps], long-standing persistent/permanent [Pm]) was determined by chart review. The t/s decreased with age (P <.00001). Subjects with a history of AF (n = 379 [10.6%] had shorter telomeres (mean t/s ± SD = 0.87 ± 0.29) compared to subjects without AF (mean t/s 0.95 ± 0.32, P <.0001). The association remained after adjustment for age (P = .017) and cardiovascular risk factors (P = .016). AF subtype was determined for 277 subjects; 110 (39.7%) had Px AF, 65 (23.5%) Ps, and 102 (36.8%) Pm AF. Mean t/s did not differ between Ps, Pm, and subjects without AF (0.94 ± 0.40, 0.94 ± 0.27, and 0.95 ± 0.32, respectively). However, the mean t/s for Px (0.81 ± 0.22) was significantly shorter than for Ps (P = .026), Pm (P = .004), or subjects without AF (P <.0001). The present study supports an association between Px AF and TL. Short TL may be a previously unrecognized risk factor for AF with potential applications in diagnosis and therapy.